Effects of a multifactorial injuries prevention program in young Spanish football players - Chena, M.; Rodriguez, M. L.; Bores, A. J.; Ramos-Campo, D. J. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The high injury rate in football has highlighted the need to research strategies that allow the modification of the dynamic risk factors. Most of the preventive proposals have focused on standardized protocols. However, the aim of this study was to evaluate the effect of a multifactorial injuries prevention program (MC-7) in Spanish football players. METHODS: A total of 219 Spanish football male players aged 16-23 were enrolled. The study was conducted over two consecutive seasons (2012-2013, 2013-2014). The first season was the control season (SC) and the second one was the experimental season (ES). Injuries were recorded prospectively during the two seasons in accordance with the criteria established by the consensus statement. During CS the injuries were just observed, while during ES, the players participated in the MC-7: training methodology, specific warm-up protocol (FIFA 11+), basic injury recovery strategies, continuous training of coaches, conferences for parents/family and education sessions for players. RESULTS: The frequency of injuries was significantly reduced by 63.8% in the ES. Muscle-tendon and joint injuries were reduced by 65% and 56.7% respectively, with a significant decrease in the lower-limbs injuries. The incidence of injuries was reduced by 71.4%, with significant differences in the typology, location and severity of injuries. CONCLUSIONS: The rate of injury in football is reduced when multifactorial strategies are applied. Reducing the frequency and severity of injuries allowed players to greatly increase their available for sports practice.